Preparation of antiviral sera for immunofluorescence on infected tissue culture - Herd, Susan (1971)
Antisera were prepared in rabbits against parainfluenza types 1, 2, and 3, respiratory syncytial, herpes, and adenoviruses, either by intranasal administration or by injection of virus grown in RK(13) cells. These antisera gave satisfactory results when used for immunofluorescence by the indirect method on virus in tissue culture. No absorption of the antiviral serum was carried out.